2018
DOI: 10.1038/s41582-018-0051-6
|View full text |Cite|
|
Sign up to set email alerts
|

Spinocerebellar ataxias: prospects and challenges for therapy development

Abstract: The spinocerebellar ataxias (SCAs) comprise more than 40 autosomal dominant neurodegenerative disorders that present principally with progressive ataxia. Within the past few years, studies of pathogenic mechanisms in the SCAs have led to the development of promising therapeutic strategies, especially for SCAs caused by polyglutamine-coding CAG repeats. Nucleotide-based gene-silencing approaches that target the first steps in the pathogenic cascade are one promising approach not only for polyglutamine SCAs but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
199
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 206 publications
(224 citation statements)
references
References 211 publications
(195 reference statements)
2
199
1
5
Order By: Relevance
“…Spinocerebellar ataxias are a large group of neurodegenerative disorders of which the most prevalent ones are caused by the expansion of a glutamine-encoding CAG repeat in the respective genes (Paulson et al 2017). Their inheritance pattern is mostly autosomal dominant and the repeat size is linked to the disease penetrance (Ashizawa et al 2018). Patients typically present with gait imbalance associated with limb incoordination and problems with gross and fine motor skills.…”
Section: Polyq Repeat Expansion-spinocerebellar Ataxiamentioning
confidence: 99%
“…Spinocerebellar ataxias are a large group of neurodegenerative disorders of which the most prevalent ones are caused by the expansion of a glutamine-encoding CAG repeat in the respective genes (Paulson et al 2017). Their inheritance pattern is mostly autosomal dominant and the repeat size is linked to the disease penetrance (Ashizawa et al 2018). Patients typically present with gait imbalance associated with limb incoordination and problems with gross and fine motor skills.…”
Section: Polyq Repeat Expansion-spinocerebellar Ataxiamentioning
confidence: 99%
“…Despite the implementation of several clinical trials based on mechanistic studies of the pathogenesis of SCA, currently there is no specific medication approved for treating SCA patients (Ashizawa, Oz, & Paulson, 2018). Therapeutic approaches targeting voltagegated K + channels have been implicated in the treatment for cancer, arrhythmia, multiple sclerosis, and epilepsy (Wulff, Castle, & Pardo, 2009).…”
Section: Dominant-negative Mechanisms Of Sca19/22mentioning
confidence: 99%
“…It has been shown in laboratory-based assessments that measures of spatial and temporal movement variability allow distinctively to capture and characterize the specificities of ataxic gait [3][4][5][6][7][8][9][10] . Moreover, they allow to quantify disease severity even at preclinical stages of DCA 11,12 and to capture treatment-induced improvements in a fine-grained fashion [13][14][15] , thus suggesting a high potential as both progression and treatment response parameters in the upcoming treatment trials [16][17][18] . Recently, first studies showed that such measures of spatio-temporal variability characterizing ataxic gait can also be captured using wearable inertial sensors in clinical assessments 19,20 .…”
Section: Discussionmentioning
confidence: 99%